OPTIMALISASI KUALITAS PRODUK AMDK MELALUI PENDEKATAN SIX SIGMA DALAM UPAYA MENURUNKAN CACAT PRODUK - Raodah Raodah; Irin Ramdhani; Nurul Ilmi; Erniyani Erniyani; Dwi Handayani (Universitas Putera Batam, 2026)
Product quality is a crucial factor in enhancing the competitiveness of the manufacturing industry, particularly in the Bottled Drinking Water (BDW) industry. This study aims to optimize the quality of bottled drinking water products through the Six Sigma approach in an effort to reduce product defect rates. The method employed is Six Sigma with the DMAIC (Define, Measure, Analyze, Improve, and Control) framework. The data used consist of product defect records collected over a three-month period, including broken bridge defects, tilted caps, standing caps, and overpressure defects. In the measure phase, defect rates, Defects Per Million Opportunities (DPMO), and sigma levels were calculated to evaluate the performance of the production process. The analyze phase revealed that broken bridge defects were the dominant type of defect based on Pareto diagram analysis, making them the primary focus for improvement efforts. Root cause analysis using a cause-and-effect (fishbone) diagram indicated that the main contributing factors originated from machine, method, and human aspects. Furthermore, in the improve phase, several corrective actions were proposed, including machine torque adjustment, operator training, implementation of Standard Operating Procedures (SOPs), and improvement of raw material quality. The control phase was conducted by establishing operational standards and process monitoring systems to ensure the sustainability of improvements. The results demonstrate that the implementation of Six Sigma provides a systematic solution for reducing product defects and continuously improving the quality of bottled drinking water products.